Insuficiencia respiratoria aguda en paciente masculino de 68 años con antecedentes de hipertension arterial. - Cadena Acosta, Darwing Edison (2020)
Respiratory failure is a complication characterized by the inability of the body to maintain arterial levels of oxygen and carbon dioxide. The present clinical case is a 68-year-old patient, who was admitted with dyspnea and tachypnea as the main symptoms, in addition to a history of arterial hypertension. We must bear in mind that respiratory failure is not a pathology, but a complication resulting from other types of pathologies that may be affecting the body. Laboratory tests such as chest x-rays and blood gases were the main diagnostic measures to verify or rule out other types of pulmonary involvement. After the analysis of the results of the examinations and x-rays requested, it is determined based on the blood and radiological results where values are shown above normal, so the doctor orders to enter it to provide treatment routinely in order to this better. In the elderly, it is among the first causes of mortality with an infectious principle at a general level in the world, this is due to the fact that the mortality rate of this disease doubles as the age advances, presenting significant morbidity. Carrying out this work is feasible, since it will help us to gather relevant information about the incidence of this disease in older adults, and thus generate a point of reference for future studies of this type or more in-depth research on this topic. today it is something that should be given a relevant position in medical studies.